PENGARUH WADAH MEMASAK YANG BERBEDA TERHADAP SIFAT MUTU ORGANOLEPTIK DAGING AYAM BUMBU RINTEK WUUK (RW) - Kasih, Trifonia; Tinangon, Meilani R.; Sembor, Sofi M.; Rotinsulu, Merri D. (Universitas Sam Ratulangi, 2020)
THE EFFECT OF DIFFERENTÂ Â Â COOKING CONTAINER ON THEÂ SENSORIC QUALITY OF Â TRADITIONAL â€œRINTEK WUUKâ€ (RW) SEASONING CHICKEN. The purpose of this study was to determine the effect of different cooking containers on the organoleptic qualities of RW seasoning chicken meat. This study used a completely randomized design (CRD) with three treatments and 40 replications (untrained panelists). The treatments were arranged as follows: R1 = bamboo container, R2 = earthen pot container, R3 = pan container. The results and further testing of the doubled duncan region showed that different cooking containers gave a real difference (PË‚0.05) to the taste but did not give a difference (PËƒ0.05) to the color, aroma, and texture, but generally accepted by the panelists. Based on data analysis and discussion for all variables it can be concluded that Rintek Wuuk (RW) seasoned chicken meat cooked using bamboo containers is preferred.Â Keywords: Cooking container, Chicken meat, RW seasoning, Organoleptic